Designing Innovative Online Lessons to Foster Piano Playing Skills for Beginners with No Prior Experience - Guobin, Zhou; Suttachitt, Narutt; Charoensloong, Thitinun (Journal of Posthumanism, 2025)
This research aims to design innovative online lessons for fostering piano playing skills in beginners with no prior experience. The study addresses the challenges and opportunities in teaching piano remotely, focusing on the key variables of lesson design, personalized feedback, and student engagement. A mixed-methods approach was employed, combining qualitative interviews with five piano teaching experts and quantitative analysis using data from 123 students who had no previous piano experience. The qualitative phase involved interviews to explore expert opinions on effective lesson components, which informed the development of the online lessons. In the quantitative phase, a questionnaire was administered to students to evaluate the effectiveness of the lessons. Data analysis was performed using SmartPLS to assess the relationships between the variables and test the proposed hypotheses. The findings show that all hypotheses were accepted, indicating that lesson design, feedback mechanisms, and engagement strategies significantly contribute to the success of online piano lessons for beginners. This research fills a gap in the literature by providing insights into designing effective online piano lessons tailored to beginners, a largely underexplored area. Its originality lies in the integration of expert feedback with empirical student data, offering practical recommendations for enhancing online music education for novice learners.